Pendampingan Ibu Hamil Sebagai Upaya Meningkatkan Perilaku Kesehatan dan Persalinan di Fasilitas Kesehatan - Isnaeni, Wilya; Wijaya, Ida Bagus Putra; Rasyid, Irna; Suprapti, Suprapti; Aryastami, Ni Ketut; Sudikno, Sudikno (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Low coverage of antenatal care (ANC) and mothers’ delivery conducted not in the health care facilities were two major problems related to maternal health care in of the West Nusa Tenggara Province. The accompaniment to pregnant women could be solution to prevent the risks of pregnancy by increasing the coverage of ANC and directing mother to deliver in health care facilities. This study aims to study the effect of mentoring pregnant women on maternal health behavior during pregnancy until delivery. A quasi-experiment study was conducted in two districts namely East and Central Lombok. Two public health centers ‘Puskesmas’ were selected in each districts. They differed as the intervention and controlled health centers. The criteria for the both health centers were having high number of pregnant women, but low coverage of maternal health services. The control health centers defined as having the closest distance from the intervention one. Study population of this study were all pregnant women in the study area. Sample were selected for those women with the gestational age of 24-26 weeks and willing to be accompanied further or neither not delivery. The total of 130 women were randomly selected from the study population. Results showed the accompaniment of pregnant women was able to increase the score of health behavior as compare to the control group. Pregnant women with accompaniment were 30 times higher chance of better health behavior (OR=30.89; 95%CI=10.72-84.40), and 3 fold prefer to deliver at health facilities (OR=2.89; 95%CI=1.16-7.21). Other positive impact of accompaniment was the obedience of iron pill at least 90 tablets, as well as food supplementation taken. Student accompaniment brought a positive impact to pregnant women on health behavior and delivery in health facility.